2016
DOI: 10.7863/ultra.15.07009
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography of the Spleen for Monitoring Transjugular Intrahepatic Portosystemic Shunt Function

Abstract: A Pilot Studyhe transjugular intrahepatic portosystemic shunt (TIPS) is used for management of refractory acute variceal hemorrhage and intractable ascites in late-stage liver diseases with portal hypertension. 1 In addition to monitoring the clinical status, it is important to monitor TIPS hemodynamic function objectively. 2,3 Although the portosystemic pressure gradient (PPG) and hepatic venous pressure gradient are still considered the reference standards for diagnosis and monitoring of portal hypertension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
(57 reference statements)
3
11
0
Order By: Relevance
“…The increase in SS after the reduction of the stent diameter observed in the two patients with persistent hepatic encephalopathy suggests that in patients submitted to TIPS, this parameter may be used to monitor the shunt function, confirming the observation of Gao et al 35 However, the efficacy and the sensitivity of splenic stiffness in detecting the occurrence of a shunt dysfunction after TIPS needs further investigations.…”
Section: Discussionsupporting
confidence: 81%
“…The increase in SS after the reduction of the stent diameter observed in the two patients with persistent hepatic encephalopathy suggests that in patients submitted to TIPS, this parameter may be used to monitor the shunt function, confirming the observation of Gao et al 35 However, the efficacy and the sensitivity of splenic stiffness in detecting the occurrence of a shunt dysfunction after TIPS needs further investigations.…”
Section: Discussionsupporting
confidence: 81%
“…(9)(10)(11)(12)(13)(14)(15) While it has been shown that liver and spleen stiffness might detect changes in hepatic venous pressure gradient after nonselective beta-blockers, the data were not as conclusive after TIPS. (16)(17)(18)(19) Importantly, a larger recent study could not sufficiently explain the reason behind the change of liver stiffness after TIPS. (20) This is probably due to the fact that liver stiffness is a result of various different factors, especially blood (arterial and venous) pressure, inflammation, and fibrosis.…”
mentioning
confidence: 94%
“…Liver stiffness, measured by either transient elastography (TE)—recently approved by the Food and Drug Administration in the United States—or shear wave elastography (SWE), is a useful parameter in the diagnosis of clinically significant portal hypertension and varices requiring treatment . While it has been shown that liver and spleen stiffness might detect changes in hepatic venous pressure gradient after nonselective beta‐blockers, the data were not as conclusive after TIPS . Importantly, a larger recent study could not sufficiently explain the reason behind the change of liver stiffness after TIPS .…”
mentioning
confidence: 99%
“…Other authors suggest that Transient Elastography is a user-friendly approach to the evaluation of spleen stiffness in primary myelofibrosis patients as a marker of the bone marrow fibrosis status and as a means of monitoring their response to innovative myelofibrosis therapies ( 40 ) . Another example of spleen elastography utilization is monitoring of transjugular intrahepatic portosystemic shunt (TIPS) function; it has been proven that splenic SWV is compatible with splenoportal venous velocity in the quantitative monitoring of the TIPS function and in determining TIPS dysfunction ( 41 ) .…”
Section: Other Applicationsmentioning
confidence: 99%